Mediterráneo. Hacia un nuevo Orden del Discurso. Teorías del conflicto, Conflicto de teorías - Reyes, Román (Nómadas. Critical Journal of Social and Juridical Science, 2017)
From geographical and cultural positions, often antagonistic, it is possible to project convergent looks. The different approaches distort the observed mean. The distortion is accumulation of perspectives over time, but it is also reconversion of spacesand situations. The relationships between objects and individuals which watch are also changeable, because the interest is neitherstable nor homogeneous.